2015
DOI: 10.4161/2162402x.2014.982382
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thein vivoimmune network of IDO, tryptophan metabolism, PD-L1, andCTLA-4in circulating immune cells in melanoma

Abstract: In melanoma, both the induction of immunosuppression by tumor cells and the inflammatory antitumor response can induce an upregulation of counter-regulatory mechanisms such as indoleamine 2,3-dioxygenase (IDO), programmed death-ligand 1 (PD-L1) and CTLA-4 C regulatory T-cells (Tregs) in the tumor microenvironment. Even though these immunosuppressive mediators are targets for immunotherapy, research investigating their expression in the peripheral blood is lacking. We therefore, performed flow cytometry on PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 29 publications
7
65
1
4
Order By: Relevance
“…Modulation of microenvironment tryptophan availability through increased IDO activity is a well-characterized mechanism of immune regulation by tolerogenic DC (19). While IDO activity has been demonstrated for human pDC (45)(46)(47) and CD1c ϩ mDC (48), we did not measure DC-specific IDO expression in this study, and the observed drastic increase in the plasma KT ratio is unlikely to be attributable to DC alone. Mouse models of malaria have …”
Section: Discussioncontrasting
confidence: 43%
“…Modulation of microenvironment tryptophan availability through increased IDO activity is a well-characterized mechanism of immune regulation by tolerogenic DC (19). While IDO activity has been demonstrated for human pDC (45)(46)(47) and CD1c ϩ mDC (48), we did not measure DC-specific IDO expression in this study, and the observed drastic increase in the plasma KT ratio is unlikely to be attributable to DC alone. Mouse models of malaria have …”
Section: Discussioncontrasting
confidence: 43%
“…In line with our results, a recent study showed that exhausted T cells are associated with increased CTLA-4 expression in MDSCs in melanoma. 34 However, it remained unclear whether CTLA-4 inhibits tumor growth in a MDSCs and M2 macrophage dependent manner. In our mouse model, we observed that blockade of CTLA4 reduced the number of MDSCs and M2 macrophages in the tumor and the immune organ.…”
Section: Discussionmentioning
confidence: 99%
“…В основном супрессорное влияние IDO на T-клетки связывают с истощением незаме-нимой аминокислоты триптофана, при отсутствии которой наблюдается остановка клеточного цикла [28,29]. В последнее время имеются предположения, что механизм IDO более сложен и супрессивными свойствами обладают метаболиты триптофана.…”
Section: воздействие миелоидных супрессоров на иммунный ответunclassified